Fractional Exhaled Nitric Oxide and Nanomaterial Exposure in Workplaces - Iavicoli, Ivo; Fontana, Luca; Leso, Veruscka; Macrini, Maria Carmela; Pelclova, Daniela (Current medicinal chemistry, 2020)
BACKGROUND: The widespread application of engineered nanomaterials (ENMs) and the increasing likelihood of general and occupational exposure raised concerns on their possible human health impact. ENMs, in fact, may induce alterations in different organ systems, and particularly in the respiratory tract. This makes it important to identify possible biomarkers of early lung effect in exposed workers. In this regard, the possibility to use the fractional exhaled levels of nitric oxide (FENO) in biological monitoring has attracted considerable interest. OBJECTIVE: To comprehensively assess the role of FENO as a possible biomarker of lung effect in ENM exposed workers. METHODS: A systematic search was performed on Pubmed, Scopus, and ISI Web of Knowledge databases according to the PRISMA guidelines. RESULTS: Seven studies investigated FENO in workers exposed to different kinds of metal- (i.e. silver and gold), metal oxide- (titanium and silica dioxide), and carbon-based ENMs (carbon nanotubes). In general, no significant alterations were detected between exposed workers and controls. CONCLUSION: Definite conclusion on the function of FENO in occupational biological monitoring cannot be extrapolated due to the limited number of available studies and the small size of investigated populations. Additionally, the lack of environmental monitoring data and the fragmented knowledge on ENM modes of action prevent to establish dose-response relationships. Future research appears necessary to deeply define the possibility to employ FENO as an early biomarker of lung effects taking in consideration possible occupational exposure issues, i.e. differently characterized ENMs and work tasks, as well as individual influencing factors, i.e. smoking and atopy.
Keywords: nanostruktury; Nanotubes, Carbon; Exhalation; Humans; oxid dusnatý; Nitric Oxide; nanotrubičky uhlíkové; Fractional exhaled nitric oxide; biomarkers; nanomaterials; exhaled breath condensate; Nanostructures; occupational exposure; vydechnutí; biologické markery; dechové testy; Breath Tests; pracoviště; lidé; Biomarkers; Workplace; nanoparticles